(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Identify drug-related problems in prescriptions for outpatient hypertension treatment at a district hospital in Ho Chi Minh city in 2023. Subjects and methods: A retrospective cross-sectional descriptive study conducted on 420 randomly selected outpatient hypertension treatment prescriptions at a district-level hospital in Ho Chi Minh city in 2023. Data were processed using Microsoft Excel 2016 and SPSS 20.0 software. Results: The patients in the study sample mostly belonged to the high-risk group, had multiple comorbidities, used three or more types of drugs, with over 80% of prescriptions involving combination antihypertensive drugs. 27.9% of prescriptions recorded at least one drug-related problem. Common drug-related problems includes: drugs not indicated despite diagnosis (17.6%); prescriptions with contraindications (6.7%), including two noteworthy cases: diuretics prescribed for gout patients (6.2%) and beta-blockers prescribed for asthma patients (0.2%); incorrect drug dosage (5.5%); incorrect drug administration (3.1%); missing diagnosis (2.1%); prescriptions with severe drug interactions (1.2%). 44.2% of cases had drug combinations that did not comply with recommendations for patients with hypertension and comorbid conditions such as coronary artery disease, type 2 diabetes, or chronic kidney disease. Conclusion: The study describes the sample, records, identifies, and analyzes the rate of drug-related problems in hypertensive patients treated at the hospital, as well as cases of drug combinations that do not comply with recommendations for patients with hypertension and comorbid conditions.